ANALISIS KEMAMPUAN LITERASI MATEMATIKA BERDASARKAN PADA ASPEK NORMA SOSIOMATEMATIK - Cahayani, Ayu Budi Cahayani Budi; Maarif, Samsul (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2023)
This research aims to investigate the literacy abilities of students based on sociomathematics norms. The research method used is a case study. The subjects of this research consist of 3 selected students categorized as high, medium, and low achievers. The research incorporates a questionnaire, a written test, and interviews to assess the students' mathematical literacy abilities and their understanding of sociomathematics norms. The analytical technique employed includes the Rasch model for the questionnaire and test data, while the interview results were analyzed through reduction analysis, data gathering, and conclusions were facilitated using the MAXQDA application. The findings of the research indicate the following: 1) Students in the high category of mathematics literacy abilities also demonstrate high sociomathematics norms, and the same trend applies to the medium and lower categories; 2) The indicators of students' mathematics literacy abilities predominantly fall within levels 1, 2, and 4; 3) The indicators of sociomathematics norms among students primarily encompass mathematics experience, mathematics differences, and the effectiveness of mathematics. This research serves as a reference for readers seeking insights into the topic